Exploring the factors affecting the adoption of mobile wallet for digital payment in Singapore: analysis of the effect of digital literacy and social media - Nalliah, Mahimai Chelvan (2022)
This research explores the factors affecting the adoption of mobile wallets in Singapore. Mobile wallets have risen to prominence in recent years as a viable alternative to established payment methods in several countries. Mobile technology has been evolving toward implementing near-field communication technology into the mobile wallet, envisioned initially as a replacement for the traditional wallet. Singapore was the early nation to embrace this digital revolution and was well-positioned to become the world's leading digital economy. With a solid and stable government ranked among the top for innovation, world-class infrastructure and institutions, and an enormously educated and skilled workforce, it was projected that Singapore would be on a smooth path to embrace this digital transformation. However, a study conducted by SMU showed that 40 percent of all transactions in Singapore involved cash, and cash in circulation was 10 percent of Singapore's total GDP. This has raised significant concern for government policymakers. In addition to this, Singapore is sitting on a ticking demographic time bomb when Singapore became an aging society in 2017, with 14 percent of the population being elderly above 65 years old and not digitally savvy. Singapore's electronic payment and mobile wallet journey push are in response to the changing outlook impacting jobs, economic growth, and the broadening of social inequality. This study aims to determine the factors influencing user engagement and willingness to use mobile wallet services in Singapore. The data was collected via Survey Monkey, and data screening was done to choose 207 valid respondents’ data to prove the hypotheses constructed on the UTAUT2 model augmented with digital literacy and social media. Respondents consist of 104 males and 103 females. The data was validated using exploratory and confirmatory factor analyses using SEM. This study discovered that Price Value (PV) had the most strongly significant factor affecting individual behavior willingness to use a mobile wallet in Singapore. Next were Hedonic Motivation, Digital Literacy Skills, and Performance Expectancy. The findings of this study can be used in various ways by government policymakers, mobile wallet developers, businesses, and industry leaders to make better product decisions related to the mobile wallet.